Evidence of a chimpanzee-sized ancestor of humans but a gibbon-sized ancestor of apes. Issue 1 (December 2017) - Grabowski, Mark; Jungers, William
Abstract Body mass directly affects how an animal relates to its environment and has a wide range of biological implications. However, little is known about the mass of the last common ancestor (LCA) of humans and chimpanzees, hominids (great apes and humans), or hominoids (all apes and humans), which is needed to evaluate numerous paleobiological hypotheses at and prior to the root of our lineage. Here we use phylogenetic comparative methods and data from primates including humans, fossil hominins, and a wide sample of fossil primates including Miocene apes from Africa, Europe, and Asia to test alternative hypotheses of body mass evolution. Our results suggest, contrary to previous suggestions, that the LCA of all hominoids lived in an environment that favored a gibbon-like size, but a series of selective regime shifts, possibly due to resource availability, led to a decrease and then increase in body mass in early hominins from a chimpanzee-sized LCA. The pattern of body size evolution in hominids can provide insight into historical human ecology. Here, Grabowski and Jungers use comparative phylogenetic analysis to reconstruct the likely size of the ancestor of humans and chimpanzees and the evolutionary history of selection on body size in primates.